2023
DOI: 10.1186/s12877-023-04289-z
|View full text |Cite
|
Sign up to set email alerts
|

Orthogeriatric co-managements lower early mortality in long-lived elderly hip fracture: a post-hoc analysis of a prospective study

Feng Gao,
Gang Liu,
Yufeng Ge
et al.

Abstract: Objective To evaluate the clinical effectiveness of orthogeriatric co-management care in long-lived elderly hip fracture patients (age ≥ 90). Methods Secondary analysis was conducted in long-lived hip fracture patients between 2018 to 2019 in 6 hospitals in Beijing, China. Patients were divided into the orthogeriatric co-management group (CM group) and traditional consultation mode group (TC group) depending on the management mode. With 30-day mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Regular orthogeriatric input has been demonstrated to be associated with significant improvement in decreasing length of hospital stay, reduction of financial burden, decreased time to operation, reduced mortality, early mortality, and improvement in early mobility [15][16][17][18][19][20][21]. This study demonstrates that the implementation of regular orthogeriatric review is associated with a significant decrease in non-surgical site infections (NSSIs) only in individuals with severe cognitive impairment and infection-associated mortality.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Regular orthogeriatric input has been demonstrated to be associated with significant improvement in decreasing length of hospital stay, reduction of financial burden, decreased time to operation, reduced mortality, early mortality, and improvement in early mobility [15][16][17][18][19][20][21]. This study demonstrates that the implementation of regular orthogeriatric review is associated with a significant decrease in non-surgical site infections (NSSIs) only in individuals with severe cognitive impairment and infection-associated mortality.…”
Section: Discussionmentioning
confidence: 88%
“…Importantly, Lisk et al, 2023 showed that orthogeriatric liaison services were associated with a significant decrease in the length of hospital stay, and the introduction of the service was also linked to savings of EUR 2.7 million per 1000 patients [15]. Several studies have indicated that orthogeriatric liaison services are associated with improvements in the length of hospital stay, decreased time to surgery, reduced early mortality, and improvements in early mobility [16][17][18][19][20][21]. The success of orthogeriatric services in acute hospitals or rehabilitation units depends on its multidisciplinary approach, including nutritional support [22,23].…”
Section: Introductionmentioning
confidence: 99%